Age-related fatigability in knee extensors and knee flexors during dynamic fatiguing contractions - Wu, R.; De Vito, G.; Lowery, M. M.; O´Callaghan, B. (Journal of Electromyography and Kinesiology, 2022)
This study investigated the effects of dynamic knee extension and flexion fatiguing task on torque and neuromuscular responses in young and older individuals. Eighteen young (8 males; 25.1 ± 3.2 years) and 17 older (8 males; 69.7 ± 3.7 years) volunteered. Following a maximal voluntary isometric contraction test, participants performed a fatiguing task involving 22 maximal isokinetic (concentric) knee extension and flexion contractions at 60°/s, while surface EMG was recorded simultaneously from the knee extensors (KE) and flexors (KF). Fatigue-induced relative torque reductions were similar between age groups for KE (peak torque decrease: 25.15% vs 26.81%); however, KF torque was less affected in older individuals (young vs older peak torque decrease: 27.6% vs 11.5%; p < 0.001) and this was associated with greater increase in hamstring EMG amplitude (p < 0.001) and hamstrings/quadriceps peak torque ratio (p < 0.01). Furthermore, KE was more fatigable than KF only among older individuals (peak torque decrease: 26.8% vs 11.5%; p < 0.001). These findings showed that the age-related fatigue induced by a dynamic task was greater for the KE, with greater age-related decline in KE compared to KF.